When roads challenge futures: first reflections about mobility in the city of José Bonifácio (SP) - de Trói, Marcelo; Reis, Weber (Revista Nacional de Gerenciamento de Cidades, 2022)
Based both on an observation job occurred from 2018 to 2021 and on informal conversations with mobile agents in José Bonifácio, a municipality in the countryside of São Paulo State, this text seeks to circumscribe a research field and to point out ways for future research on mobility. The text demonstrates how mobility, subjectivity, culture, and urban space work in a small city. We observed how some changes happened in the last decades regarding the ways of moving in this city, which resulted in lifestyle and culture changed, as well. Even without claiming to be definitive, we attempted to understand how the bicycle became the most popular mode of transportation in activity. Historical advantages regarding this mode can be used in order to build a more sustainable city in tune with the new demands of climate change.